PENERAPAN MEDIA REALIA DALAM PENINGKATAN KOMPETENSI GURU SMK PADA KOMPETENSI MERAWAT DAN MEMPERBAIKI TRANSMISI OTOMATIS - Kir Haryana; Tafakur Tafakur; Muhkamad Wakid (INOTEKS : Jurnal Inovasi Ilmu Pengetahuan, Teknologi, dan Seni, 2022)
Nowadays, vocational education program, SMK need to be encouraged to higher quality in order to fulfill competitive working area. Limitations of teachers competences should be minimized by teachers competences development programs. This lecturer dedication program aims to: (1) Increase teachers competence in maintaining, repairing and overhauling automatic transmissions using planetary gear unit realia media. (2) produce teaching handbooks document about automatic transmission material developed by teachers for teaching in TKRO Vocational Schools. The audiences of this program are 35 Automotive Light Vehicle Engineering Study Program teachers in the Yogyakarta City and Bantul Regency areas. The program was carried out using the theoretical training method and continued with the practical training in the maintenance and repair of the automatic transmission system. This training is based on the competencies needed in maintenance work and repair of automatic transmission of vehicles. Based on the program results, it can be concluded that (1) the competence of teachers in maintaining and repairing automatic transmission through this training can be increased. It can be seen from the average pretest and posttest of the trainees significantly increased. (2) Automatic transmission training supports teachers to be able to develop automatic transmission practice learning documents in accordance with the basic competencies of SMK.